BAGAIMANA MENDESAIN PEMBELAJARAN LITERASI DAN NUMERASI YANG INKLUSIF DI SEKOLAH DASAR? - Arif Widodo; Dyah Indraswati (Unika Santu Paulus Ruteng, 2022)
Empirical facts show that literacy and numeracy abilities are very diverse. This study aims to analyze the design of inclusive learning according to the diversity of students' abilities. The research location is SDN Selebung 2, Central Lombok Regency. The type of research used is a case study. Collecting data using observation, interviews, questionnaires, and documentation. The results of the study found that the inclusive literacy and numeracy learning model was teaching at the right level (TaRL). Students are divided into several groups according to their ability level. The stages of the TaRL learning model include initial assessment, grouping students, and learning according to level. The application of the level-based learning model shows an improvement in the learning process. Indicators of the success of the application of the model can be seen from the increase in students' literacy and numeracy skills, as well as the large number of students who give positive responses to ability level-based learning.